Enhancement of ghrelin-signaling system by Rikkunshi-To attenuates teriparatide-induced pica in rats - Kouichi Yamamoto; Yukihiro Isogai; Takayuki Ishida; Keisuke Hagihara (Elsevier, 2018)
Teriparatide is clinically used for the treatment of osteoporosis; however, nausea is often observed in patients. Its insufficient control affects the ability to continue teriparatide therapy. Rikkunshi-To (RKT), a traditional Japanese herbal medicine, improves the gastrointestinal function via activation of the ghrelin-signaling system. We investigated the therapeutic effects of RKT on teriparatide-induced nausea in rats and the involvement of ghrelin in these effects. We previously reported that ovariectomized rats showed pica (kaolin ingestion), a behavior that can be used to assess nausea in rats, after the subcutaneous administration of teriparatide; thus, the behavior was used as an index of nausea. Ovariectomized rats were fed diets with or without RKT (1%) for 2 weeks, and then they received the subcutaneous injection of teriparatide (400 μg/kg). Teriparatide significantly increased the incidence of pica, while suppressing intestinal motility and plasma ghrelin levels in rats fed normal diets; however, rats fed diets with RKT showed improvements in all of the teriparatide-induced adverse reactions. These therapeutic effects were antagonized by a ghrelin receptor antagonist ([D-Lys3]-GHRP-6; 200 nmol/rat). These findings suggest that the enhancement of ghrelin-signaling is involved in RKT's therapeutic effect, and that RKT is a potentially useful treatment for teriparatide-induced nausea. Keywords: Ghrelin, Nausea, Pica, Rikkunshi-To, Teriparatide